The cold-water coral Solenosmilia variabilis as a paleoceanographic archive for the reconstruction of intermediate water mass temperature variability on the Brazilian continental margin - Endress, Serafina Chiara; Schleinkofer, N.; Schmidt, A.; Tracey, D.; Frank, Norbert; Raddatz, J. (Frontiers in Marine Science, 2022)
Recent oceanographic observations have identified significant changes of intermediate water masses characterized by increased temperatures, lowered pH and deoxygenation. In order to improve our understanding as to how these changes may impact deep-sea ecosystems one important strategy is to reconstruct past oceanic conditions. Here we examine the applicability of the scleractinian cold-water coral Solenosmilia variabilis as a marine archive for the reconstructions of past intermediate water mass temperatures by using Lithium (Li)/Magnesium (Mg) ratios. In particular, our study addresses 1) the calibration of Li/Mg ratios against in-situ temperature data, 2) the reconstruction of past intermediate water mass temperatures using scleractinian coral fossil samples from the Brazilian continental margin and 3) the identification of intraspecies variability within the coral microstructure. Results showed that Li/Mg ratios measured in the skeletons of S. variabilis fit into existing Li/Mg-T calibrations of other cold-water scleractinian. Furthermore, the coral microstructure exhibits interspecies variability of Li/Ca and Mg/Ca ratios were also similar to what has been observed in other cold-water scleractinian corals, suggesting a similar biomineralization control on the incorporation of Li and Mg into the skeleton. However, the Li/Mg based temperature reconstruction using fossil samples resulted in unexpectedly high variations >10 degrees C, which might not be solely related to temperature variations of the intermediate water mass over the last 160 ka on the Brazilian continental margin. We speculate that such temperature variability may be caused by vertical movements of the aragonite saturation horizon and the associated seawater pH changes, which in turn influence the incorporation of Li and Mg into the coral skeleton. Based on these results it is recommended that future studies investigating past oceanic conditions need to consider the carbonate system parameters and how they might impact the mechanisms of Li and Mg being incorporated into skeletons of cold-water coral species such as S. variabilis.
Gesehen am 31.03.2023